ID-based threshold decryption with non-reconstruction of the private key - QIN Bao-shan 1; ZHOU Yuan2 (Tongxin xuebao)
An efficient ID-based encryption scheme called EPA was constructed and proved in the sense of plaintext awareness.Then EPA was modified to be a threshold ID-based threshold decryption scheme named ThEPA, which was featured by a property called non-reconstruction of the private key with it, a robust key escrow scheme based on ThEPA was proposed.In ThEPA, the decryption key is distributed among n decryption servers, but a single private key could not be obtained even if securities of all these distributed servers are compromised.